Insights from Computations on the Mechanism of Reduction by Ascorbic Acid of PtIV Prodrugs with Asplatin and Its Chlorido and Bromido Analogues as Model Systems. Issue 38 (10th June 2018) - Ponte, Fortuna; Russo, Nino; Sicilia, Emilia
Abstract: The elucidation of the mechanism by which the reduction of coordinatively saturated Pt IV prodrugs occurs, leading to the release of the two axial ligands, is of foremost importance, being the key step for the activation of these anticancer compounds, and addressing their synthetic strategies. A systematic DFT computational analysis of the reduction process by small biomolecules, which is supposed to occur by inner‐ or outer‐sphere electron‐transfer mechanisms, has been undertaken using the recently synthesised Asplatin Pt IV complex, c, c, t ‐[PtCl2 (NH3 )2 (OH)(aspirin)], as model system andl ‐ascorbic acid as reducing agent. Further calculations have been carried out on Asplatin analogues that should be obtained replacing the OH − ligand with Cl − and Br − . The most accredited inner‐sphere mechanistic suggestions have been explored and a recently proposed computational methodology has been applied to estimate the corresponding standard redox potentials, which cannot be directly obtained from voltammetric experiments due to the irreversibility of the platinum(IV)‐to‐platinum(II) reduction process. Abstract : Activated prodrugs : A systematic DFT computational analysis of the activation of Pt IV prodrugs by reduction as a key step has been carried out using the recently synthesised Asplatin Pt IV complex, c, c, t ‐[PtCl2 (NH3 )2 (OH)(aspirin)], and its chlorido and bromido derivatives as model systems andl ‐ascorbic acid as reducing agent. Both inner‐sphere mechanistic suggestions have been explored and standard redox potentials have been estimated based on quantum‐mechanical calculations.